136k views
4 votes
Use integration by parts to find the integrals in Exercise.
∫(6x+3)e-2x dx.

User Leonti
by
5.2k points

1 Answer

0 votes

Answer:


\displaystyle \int {(6x + 3)e^(-2x)} \, dx = -3e^(-2x) (x + 1) + C

General Formulas and Concepts:

Calculus

Differentiation

  • Derivatives
  • Derivative Notation

Derivative Property [Multiplied Constant]:
\displaystyle (d)/(dx) [cf(x)] = c \cdot f'(x)

Derivative Property [Addition/Subtraction]:
\displaystyle (d)/(dx)[f(x) + g(x)] = (d)/(dx)[f(x)] + (d)/(dx)[g(x)]

Basic Power Rule:

  1. f(x) = cxⁿ
  2. f’(x) = c·nxⁿ⁻¹

Integration

  • Integrals
  • [Indefinite Integrals] Integration Constant C

Integration Property [Multiplied Constant]:
\displaystyle \int {cf(x)} \, dx = c \int {f(x)} \, dx

U-Substitution

Integration by Parts:
\displaystyle \int {u} \, dv = uv - \int {v} \, du

  • [IBP] LIPET: Logs, inverses, Polynomials, Exponentials, Trig

Explanation:

Step 1: Define

Identify


\displaystyle \int {(6x + 3)e^(-2x)} \, dx

Step 2: Integrate Pt. 1

  1. [Integrand] Rewrite [Factor]:
    \displaystyle \int {(6x + 3)e^(-2x)} \, dx = \int {3(2x + 1)e^(-2x)} \, dx
  2. [Integral] Rewrite [Integration Property - Multiplied Constant]:
    \displaystyle \int {(6x + 3)e^(-2x)} \, dx = 3 \int {(2x + 1)e^(-2x)} \, dx

Step 3: Integrate Pt. 2

Identify variables for integration by parts using LIPET.

  1. Set u:
    \displaystyle u = 2x + 1
  2. [u] Basic Power Rule [Derivative Properties]:
    \displaystyle du = 2 \ dx
  3. Set dv:
    \displaystyle dv = e^(-2x) \ dx
  4. [dv] Exponential Integration [U-Substitution]:
    \displaystyle v = (-e^(-2x))/(2)

Step 4: Integrate Pt. 3

  1. [Integral] Integration by Parts:
    \displaystyle \int {(6x + 3)e^(-2x)} \, dx = 3 \bigg( (-(2x + 1)e^(-2x))/(2) - \int {-e^(-2x)} \, dx \bigg)
  2. [Integral] Rewrite [Integration Property - Multiplied Constant]:
    \displaystyle \int {(6x + 3)e^(-2x)} \, dx = 3 \bigg( (-(2x + 1)e^(-2x))/(2) + \int {e^(-2x)} \, dx \bigg)

Step 5: Integrate Pt. 4

Identify variables for u-substitution.

  1. Set u:
    \displaystyle u = -2x
  2. [u] Basic Power Rule [Derivative Property - Multiplied Constant]:
    \displaystyle du = -2 \ dx

Step 6: Integrate Pt. 5

  1. [Integral] Rewrite [Integration Property - Multiplied Constant]:
    \displaystyle \int {(6x + 3)e^(-2x)} \, dx = 3 \bigg( (-(2x + 1)e^(-2x))/(2) - (1)/(2) \int {-2e^(-2x)} \, dx \bigg)
  2. [Integral] U-Substitution:
    \displaystyle \int {(6x + 3)e^(-2x)} \, dx = 3 \bigg( (-(2x + 1)e^(-2x))/(2) - (1)/(2) \int {e^(u)} \, du \bigg)
  3. [Integral] Exponential Integration:
    \displaystyle \int {(6x + 3)e^(-2x)} \, dx = 3 \bigg( (-(2x + 1)e^(-2x))/(2) - (e^(u))/(2) \bigg) + C
  4. [u] Back-Substitute:
    \displaystyle \int {(6x + 3)e^(-2x)} \, dx = 3 \bigg( (-(2x + 1)e^(-2x))/(2) - (e^(-2x))/(2) \bigg) + C
  5. Factor:
    \displaystyle \int {(6x + 3)e^(-2x)} \, dx = -3e^(-2x) \bigg( (2x + 1)/(2) + (1)/(2) \bigg) + C
  6. Simplify:
    \displaystyle \int {(6x + 3)e^(-2x)} \, dx = -3e^(-2x) (x + 1) + C

Topic: AP Calculus AB/BC (Calculus I/I + II)

Unit: Integration

User Lostriebo
by
4.7k points